Pendidikan Sosial Religius Memperkuat Kerukunan Umat Hindu dan Muslim yang Multikultur di Desa Pegayaman, Buleleng, Bali - Suwendra, I Wayan (STKIP AGAMA HINDU SINGARAJA, 2023)
This study aims to: (1) find out the history of the multi-cultural Pegayaman village, (2) find out the religious social education that strengthens the harmony of Hindus and Muslims in a multi-cultural society in Pegayaman village. The sampling technique used was purposive and snowball sampling, with data collection techniques: participating observation, in-depth interviews, and documentation. While the data analysis used descriptive qualitative. The results of this study indicate that: The history of Pegayaman village cannot be separated from the leader of the King of Buleleng named Anglurah Kibarak Panji Sakti. The name is Pegayaman is taken from the gatep tree (gayam) or taken from the name of a keris, namely the gayaman which existed during the Mataram kingdom era. Social-religious education that strengthens harmony between Hindus and Muslims which is well implemented in five aspects of community activity namely, in: (1) harmonious cooperation in religious and non-religious events of different beliefs (2) democratic and social-religious-based village government leadership traditional local culture of North Bali Hindus, (3) tolerance in acting and behaving in different beliefs, (4) familiar social communication, and (5) the tradition of giving and receiving (ngejot). Everything is an acculturation of Hindu-Islamic culture that was processed hundreds of years ago from the time of the Ki Barak Panji Sakti kingdom until now. Social-religious education that strengthens this harmony needs to be preserved and implemented in other areas throughout Indonesia because Indonesia is vulnerable to SARA (ethnic, religious, racial and inter-group) conflicts.